(untitled) (Journal of Hama University, 2022)
The aim of the current research is to know the relationship between the family climate and psychological resilience among a sample of students in the second year of general secondary school in the city of Damascus, and recognize the level of psychological resilience,and family climate type, and the significance of the differences among the members of the research sample on the scale of family climate and psychological resilience according to the two variables of the research: (gender), and the researcher relied on the descriptive analytical approach, and the research sample consisted of (400) male and female students, and the researcher applied the measure of psychological resilience prepared by (Israa Shibli), The Family Climate Scale was prepared by Alaa El-Din Kafafi (2010), and the research concluded the following results: 1- There is an average level of psychological resilience among a sample of general second year secondary students 2- The existence of an abnormal family climate in the first place, inhumanity, then artificial love, and finally, the abnormal family climate. 3-There is no statistically significant correlation between psychological resilience and family climate among a sample of general second year secondary students. 4- There are no statistically significant difference between the average scores of the research sample members on the family climate scale according to the gender variable. 5- There are no statistically significant differences between the average scores of the research sample members on the psychological resilience scale according to the gender variable. The study served a set of suggestions and recommendations, the most important of which are: Designing training programs that contribute to the development of psychological resilience among adolescents, educating parents about the need to provide a normal family environment and avoiding conflicts within the family that weaken the relationship between parents and children, and holding seminars aimed at educating students about the importance of psychological resilience and a normal family climate in order for them to enjoy normal mental health.